2003
DOI: 10.1029/2003gl017373
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding magnetic holes: Hybrid simulations

Abstract: [1] One-dimensional hybrid code simulations are presented which show that magnetic field depletions of variable length and depht can be maintained over long time in mirror-stable high-b plasmas under certain conditions while magnetic compressions cannot. This suggests that short-scale magnetic holes (MHs), frequently observed in space plasmas, may be a feature of an essentially isotropic rather than a mirror-unstable plasma. This suggestion is supported by additional simulations in anisotropic plasmas which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
52
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 23 publications
9
52
3
Order By: Relevance
“…4 This appears to be tied to a bistability phenomenon, whereby nonlinear mirror structures which are magnetic holes can exist in a plasma which is below the mirror linear instability threshold. This behavior is found in both simulations 9 and fluid models based on anisotropic MHD with a Landau fluid closure. 10 Observations of magnetic holes in the solar wind and magnetosheath are consistent with them being non-propagating structures, such as mirror structures, but would be incompatible with dark soliton solutions of the Hall-MHD system.…”
Section: Introductionmentioning
confidence: 77%
“…4 This appears to be tied to a bistability phenomenon, whereby nonlinear mirror structures which are magnetic holes can exist in a plasma which is below the mirror linear instability threshold. This behavior is found in both simulations 9 and fluid models based on anisotropic MHD with a Landau fluid closure. 10 Observations of magnetic holes in the solar wind and magnetosheath are consistent with them being non-propagating structures, such as mirror structures, but would be incompatible with dark soliton solutions of the Hall-MHD system.…”
Section: Introductionmentioning
confidence: 77%
“…[3] In recent years, an alternative, ''soliton'' approach to magnetic holes, and other nonlinear structures observed in the magnetosheath of planets and comets has been developed in a series of articles by Baumgärtel [1999], Baumgärtel et al [2003], Sauer et al [2003], , and Dubinin et al [2003]. By using two-or multi-fluid equations and hybrid simulations these authors have found a variety of solitary solutions that could explain many of the reported experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Observations and numerical simulations have shown that magnetic peaks are rarely seen in mirror stable plasma because of their rapid decay, but magnetic holes could survive in a mirror stable plasma. Therefore, both peaks and holes could be observed in the magnetosheath, and most holes are observed near the magnetopause, where the plasma is mirror stable (Baumgartel et al, 2003;Travnicek et al, 2007;Soucek et al, 2008;Génot et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They therefore suggested that LMHs are probably the remnants of mirror modes structures in the solar wind (see also Winterhalter et al, 1995;Russell et al, 2008;Zhang et al, 2008Zhang et al, , 2009). Many other mechanisms have been proposed to explain the magnetic holes in the solar wind, such as the soliton approach (Baumgartel, 1999;Baumgartel et al, 2003), and theories associated with Alfvén waves (see, for example, Buti et al, 2001;Tsurutani et al, 2005). The stable solitons correspond to isotropic plasma with high β and their propagation direction is close to perpendicular to the ambient magnetic field vector.…”
Section: Introductionmentioning
confidence: 99%